Pengaruh Konservatisme Akuntansi, Inventory Intensity dan Sales Growth terhadap Tax Avoidance - Maharani, Sheli; Setyawati, Wiwit (ARZUSIN, 2024)
The study aims to examine and analyze the effect of accounting conservatisme, inventory intensity and sales growth on tax avoidance in Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange for the period 2018 to 2022. This type of research is quantitative, using secondary data. The analysis methode is panel data regression test using Microsoft Excel and Eviews 12 aplications. The population in this study are all companies Consumer Non-Cyclicals sectors. The data collection technique in this was a purposive samples, from 122 study populations to 35 were used as research samples. The results of the study show Accounting Conservatisme in Consumer Non-Cyclicals from 2018 to 2022. The result show Accounting Conservatisme and inventory intensity has no. effect on Tax Avoidance whereas Sales Growth has an effect on Tax Avoidance.